PENGARUH WAKTU HIDROLISIS PADA PEMBUATAN HIDROLISAT PROTEIN IKAN MUJAIR (Oreochromis mossambicus) TERHADAP pH, KEKENTALAN, DAYA BUIH DAN PEMBENTUKAN GEL - Haslina Haslina (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
Fish protein hydrolisatc (FPH) is expected to give more benefit in increasing added value of fish, because FPH has many advantages such as easier to digest by human, better functional properties and higher solubility.This research is aimed to find out the influences of time for enzymatic hydrolysis to pH, viscocity, foaming capacity andgel forming on hydrolysed mujair (Oreochromismossambicus) fish protein processing. A completely randomized design with 3 treatments and 4 rep I icates was used. The treatments used time hydrolysis 60, 80 and l 00 minutes. The parameters analyzed were pH, viscocity, foaming capacity and gel foaming. Result showed that the treatment significant (p<0,05)aftected pH, viscocity and foaming capacity. pH 5,42, viscocity 6,94 N/m2 and gel foaming 7, 17% was obtained in 60 minutes time hydrolysis treatment. However, fish protein hydrolysate did not perform any gel.